Thematic Structure of Eschatological Scenes in Surahs Al-Anbiyāʾ, Al-Ḥajj, and Al-Muʾminūn and Their Role in Establishing the Doctrine of Resurrection and Divine Recompense: An Analytical Study - Dr. Ihsan Ullah; Dr. Naeem Khan; Dr. Muhammad Shah Faisal (Policy Journal of Social Science Review, 2026)
This article studies eschatological scenes in Surahs al-Anbiya, al-Hajj, and al-Mu’minun, focusing on proofs of resurrection, cosmic transformation, judgment, the scales, the barzakh, and the final outcomes of Paradise and Hell. It shows that al-Anbiya opens with the nearness of reckoning, affirms universal death and return, establishes perfectly just scales, and depicts the release of Gog and Magog, the folding of heaven, and security from the greatest terror. Al-Hajj combines the earthquake of the Hour with observable proofs drawn from embryonic development and the revival of the earth, then contrasts the destinies of the two disputing parties. Al-Mu’minun links the human life-cycle to death and resurrection, establishes the barzakh and the impossibility of return, depicts the collapse of lineage-based privilege and the weighing of deeds, and places the ethical qualities of the inheritors of al-Firdaws at the beginning of the surah. The study concludes that these surahs move from warning to empirical proof and then to a concrete moral program that shapes the final destiny. Keywords: Afterlife; al-Anbiya; al-Hajj; al-Mu’minun; resurrection; barzakh; scales; Paradise and Hell.